Cross-linguistic Similarity in Foreign Language Learning. - Ringbom, Hakan (Second Language Acquisition S., 2006)
Explores the importance of cross-linguistic similarity in foreign language learning. Similarities can be perceived in the form of simplified one-to-one relationships or merely assumed. This book outlines the different roles of L1 transfer on comprehension and on production, and on close and distant target languages.